Atopic asthma after rhinovirus‐induced wheezing is associated with DNA methylation change in the SMAD3 gene promoter. Issue 8 (21st May 2018) - Lund, R. J.; Osmala, M.; Malonzo, M.; Lukkarinen, M.; Leino, A.; Salmi, J.; Vuorikoski, S.; Turunen, R.; Vuorinen, T.; Akdis, C.; Lähdesmäki, H.; Lahesmaa, R.; et al.
Abstract: Children with rhinovirus‐induced severe early wheezing have an increased risk of developing asthma later in life. The exact molecular mechanisms for this association are still mostly unknown. To identify potential changes in the transcriptional and epigenetic regulation in rhinovirus‐associated atopic or nonatopic asthma, we analyzed a cohort of 5‐year‐old children (n = 45) according to the virus etiology of the first severe wheezing episode at the mean age of 13 months and to 5‐year asthma outcome. The development of atopic asthma in children with early rhinovirus‐induced wheezing was associated with DNA methylation changes at several genomic sites in chromosomal regions previously linked to asthma. The strongest changes in atopic asthma were detected in the promoter region of SMAD3 gene at chr 15q22.33 and introns of DDO/METTL24 genes at 6q21. These changes were validated to be present also at the average age of 8 years.